PENGARUH TRI GURU, PERSEPSI MENGENAI TRI HITA KARANA, NILAI BUDAYA, DAN MOTIVASI TERHADAP PERILAKU BERWAWASAN LINGKUNGAN: Studi Kausal Pada Krama Desa Pakraman Sukawati Kecamatan Sukawati Kabupaten Gianyar Provinsi Bali - I Ketut Pande Suastawa (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2010)
This research is aim at finding out direct effect of Three Teachers (Tri Guru) on environmentally soundbehavior and to identify indirect effect of Tri Guru on environmentally sound behavior through perception aboutThree Balance Concept (Tri Hita Karana), cultural value, and motivation of villagers in Sukawati Village,District Sukawati, Gianyar Regency, Bali in 2009.Data was collected by questionnaire. The item validity of instruments was tested by Product MomentCorrelation; and the reliability was tested by Alpha Cronbach. The total sample of 251 was recruited during thestudy. Data analyses applied to test the model matching was Structural Equation Modeling.The result of analysis finds out that Tri Guru affects environmentally sound behavior significantly throughperception about Tri Hita Karana, cultural value, and motivation in greater value than direct effect of Tri Guruon environmentally sound behavior. The Model match test shows that the modified path model have achievedthe criteria of model matching, because matching test indicators achieve minimum cut-off value.Based on these findings, it could be concluded that any changing or variation on environmentally soundbehavior have been directly affected by villagers evaluation on Tri Guru, indirectly affected by perception aboutTri Hita Karana, cultural value of environmental care, and motivation to preserve the function of environment.Therefore, when we want to increase environmentally sound behavior of villagers, these factors such as TriGuru, perception, cultural value and motivation are necessary to be taken into account.